Competitiveness Analysis of the Halal value Chain in the Global Market - Budi, Yahya Ambaria (CV. Tripe Konsultan, 2025)
The halal industry has experienced exponential growth in recent decades, with a global market value reaching trillions of dollars and projected to continue increasing in line with the world's growing Muslim population. This study aimed to analyze the competitiveness of the halal value chain in the face of increasingly fierce and complex global market competition. The research methodology employs Porter's value chain analysis approach, integrated with the Diamond Model of Competitiveness framework, to identify and analyze key factors that determine competitive advantage in the halal industry.This research involves an in-depth analysis of various halal industry segments, ranging from food and beverages, cosmetics, pharmaceuticals, to Islamic financial services. The results indicate that credible and internationally recognized halal certification, the integration of digital technology into production and distribution processes, qualified human resources competent in halal standards, and adequate infrastructure support are key determinants of competitiveness in the halal industry. The findings of this study provide significant strategic implications for industry players in designing competitive strategies and for policymakers in developing a competitive and sustainable halal ecosystem in the evolving global market.